Change in critical speed but not its associated metabolic rate when manipulating muscle contraction regimen: Horizontal vs. uphill treadmill running - Carter, H.; Dekerle, J. (Science & Sports, 2013)
Introduction: This study investigated the effect of a change in muscle contraction regimen via the manipulation of treadmill gradient on critical running speed. Summary of facts: Ten participants performed a series of constant-speed exhaustive trials to model the speed-time-1 relationship using a 2-parameter equation (intercept: critical speed, CS). The treadmill gradient was either 0% (CS0%) or 10% (CS10%). A time to exhaustion (tlim) at both CS then followed in a randomised order. CS10%was lower by ~35% (2.57 ± 0.10 vs. 3.95 ± 0.15 m.s-1) yet the mean VO2 values at minute 3 of tlim did not differ significantly. There was no difference in the tlim at CS0% and CS10% (~30 minutes). However, there were some differences in the physiological responses between minute 3 and end exercise, and consequently the pattern between the two time points. Conclusion: CS is affected by a change in treadmill gradient while its associated metabolic rate isn`t. But when exercising at CS, differences in the metabolic stress over time suggests for the development of fatigue, and therefore the sustainability of CS, to be dependent on the muscular contraction regimens.